On the importance of combining bulk- and surface-active sites to maximize the catalytic activity of metal–organic frameworks for the oxidative dehydrogenation of alcohols using alkyl hydroperoxides as hydride acceptors. Issue 20 (3rd September 2020) - Gairola, P.; Millot, Y.; Krafft, J.-M.; Averseng, F.; Launay, F.; Massiani, P.; Jolivalt, C.; Reboul, J.
Abstract : The combination of spectroscopically characterized bulk- and surface-active zirconium sites makes Zr-MOF crystals efficient catalysts for alcohol dehydrogenation under mild conditions. Abstract : A series of zirconium-terephthalate UiO-66 metal–organic frameworks (MOFs) containing partially uncoordinated zirconium sites (ZrUC ) were synthesized, finely characterized by complementary physico-chemical techniques, and employed to catalyze the oxidative dehydrogenation of alcohols in the presence of tert -butyl hydroperoxide (TBHP). These sites were two-fold: bulk ZrUC sites created by reducing the content of terephthalate linkers within the framework and intrinsic ZrUC sites existing on the external surface of undefective UiO-66 crystals. The activity of both sites was evidenced by the linear dependency taking place between the activity and either the missing linkers or external surface area. Combining in one UiO-66 crystal a high density of ZrUC sites within the bulk and a high external surface area enabled the performances of the catalysts in alcohol dehydrogenation to be maximized, making the oxidation of benzyl alcohol over 90% at mild temperature ( T = 40 °C) after 2 h of reaction possible. More challenging secondary alcohols were also oxidized. The formation of Lewis acid sites at the inorganic nodes was monitored by FTIR spectroscopy of adsorbed CO. The presence of bulk and/or external ZrUC sites was further disclosed by the observation on hydrated samples of solid-state 1 H NMR signals, corresponding to the protons of terminal μ1 -OH moieties capping the ZrUC sites. Interestingly, two distinct NMR signals corresponding to the terminal μ1 -OH moieties of bulk and surface ZrUC sites were identified. Finally, a mechanism of alcohol dehydrogenation using TBHP was proposed relying on the concomitant coordination of benzyl alcohol and TBHP onto the two adjacent ZrUC sites at the zirconium cornerstones.